SOCIAL DRAMATURGY ROLES PERFORMANCE IN BATMAN THE DARK KNIGHT RISES 2012 BY CHRISTOPHER NOLAN - Asyraf Sulaeman; Sape'i Sape'i (Saksama, 2022)
This study aims to analyze the social dramaturgy aspect in the film